KEBIJAKAN PRO-RAKYAT DALAM KAMPANYE PILKADA 2024: STUDI LITERATURE REVIEW TERHADAP PROGRAM PENGENTASAN KEMISKINAN DAN PERLINDUNGAN SOSIAL - Nikijuluw, Jeanee Belthia; Maspaitella, Marthin Jonas (JURNAL BADATI, 2024)
This study aims to determine whether there is an influence of exposure to the @indozone.id Instagram account on followers' information needs. This research method uses a survey method - quantitative. Data collection techniques using a questionnaire. The theoretical approach used is the Uses and Gratification theory. The population of this study is 4.6 million people who follow the Instagram account @indozone.id where the sample is taken using the Slovin formula so that a total of 100 respondents are obtained using the Purposive Sampling technique. The results of the study show that there is an influence between exposure to the @indozone.id Instagram account and followers' information needs. Based on the results of the study, it was found that Frequency, Duration and Intensity each had an influence on information needs consisting of the current needs approach, the daily needs approach, the exhaustive needs approach, the pursuit needs approach. Data obtained and analyzed using SPSS 25.0. The results of the study show that there is a positive and significant effect of being exposed to the Instagram account @indozone.id on the information needs of followers.